Shubnikov-De Haas Effect in Cylindrical Quantum Wires under the Influence of a Laser Radiation - Huong, Nguyen Thu; Nhan, Nguyen Vu; Thuy, Dang Thi Thanh (VNU Journal of Science: Mathematics - Physics; Vol 32 No 2, 2016)
Abstract: Considering an infinite potential Cylindrical Quantum Wire (CQW)  subjected to a dc electric field , a Magnetic Field (MF)  and a laser radiation (where and  are the amplitude and the frequency of the laser radiation, respectively), the quantum kinetic equation for electron distribution function is obtained. Assuming the electron gas is non-degenerate and considering the Electron - Acoustic Phonon (AP) interaction, we achieve analytical expressions for the conductivity tensor and the Hall Coefficient (HC), which are different from those for the case of the Electron - AP interaction in a Rectangular Quantum Wire (RQW) or in Two-Dimensional Electron Gas (2DEG). The Shubnikov-de Haas (SdH) oscillations will appear. The amplitudes of SdH oscillations in the dependence of Magnetoresistance (MR) decrease with increasing MF. Numerical calculations are applied for GaAs/GaAsAl CQW to show the nonlinear dependence of the HC on the frequency of the laser radiation, and Magnetic Field (MF). Wave function and energy spectrum in a CQW are dissiminar to those in other Quantum Wires (QWs). Therefore, all numerical results are different from those in the case of QWs. The most important result is that the HC reaches saturation as the magnetic field or the EMW frequency increases. Keywords: Hall coefficient; cylindrical quantum wires; electron - optical phonon interaction; Shubnikov-de Haas oscillations.